Predictors of in-hospital mortality in infectious endocarditis. (3rd May 2023) - Rocha Carvalho, P; Bernardo, M; Moreira, I; Goncalves, F; Fontes, P; Moreira, J I
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Infectious endocarditis has a high rate of in-hospital complications and mortality, ranging between 15 and 30%. Still, there is a paucity of studies on the assessment of short-term prognosis in these patients. Purpose: To determine predictors of in-hospital mortality in patients with infective endocarditis. Methods: This was a retrospective study that included all patients hospitalized in a single centre with the diagnosis of infective endocarditis, between 2000 and 2020. The relationship between clinical, laboratory and echocardiographic variables and in-hospital mortality was evaluated. Results: A total of 161 patients were selected, 65.8% were males, with a mean age of 66.4±16.4 years. The in-hospital mortality rate was 16.8%, occurring on average after 35.0±17.5 days of hospitalization. The average length of stay was 44.5±22.8 days. Age >70 years was associated with higher mortality rate (p=0.021). There were no other significant differences between groups regarding clinical variables and comorbidities. Although not statistically significant, in-hospital mortality group had higher mean ejection fraction (57.2±2.7% vs. 54.6±12.9%). Laboratory parameters associated with mortality included isolation of Staphylococcus (p=0.019) or Enterococcus (p=0.045) in blood cultures. Though the classification of endocarditis (in native vs. prosthesis valve) did not differ between groups, the presence of perivalvular complications on echocardiography (p= 0.042) namely pseudoaneurysm (p=0.003), were more frequent in the group with higher mortality rate. There were 70 patients with indication for urgent surgery, namely for locally uncontrolled infection in 29.2%, heart failure (20.0%) and prevention of embolic events (18.1%). The existence of urgent surgical indication (p=0.009) was associated with higher mortality, and surgery during hospitalization was associated with lower mortality (p=0.011). In a multivariate regression analysis, after adjusting for all the possible confounders, the independent predictors of in-hospital mortality were the previous history of heart failure (HR = 3.29, 95%CI 1.41-7.66), chronic liver disease (HR = 4.33, 95%CI 1.23-15.30) and evolution with septic shock (HR = 6.87, 95%CI 2.89-16.39). Conclusions: The present study confirms the high mortality rate of patients with infective endocarditis, highlighting the importance of patient baseline characteristics and comorbidities, as it identified as independent predictors of in-hospital mortality the previous history of heart failure, chronic liver disease and evolution with septic shock.